Energy cost assessment of shoreside power supply considering the smart grid concept: a case study for a bulk carrier ship - Yigit, Kenan; Kokkulunk, Gorkem; Parlak, Adnan; Karakas, Arif (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
In recent years, energy-related issues have become most important for the maritime sector due to economic and environmental reasons. The use of shoreside power for serving ships while at port has been increasingly considered as a measure to improve their energy efficiency and environmental performance. In this study, the economic analysis is performed considering different marine fuels and shoreside power supply for the ship's electrical needs while at the international ports. Future predictions about shoreside power application are also discussed in the next-generation smart electrical power system for the maritime sector. For this purpose, real data of a bulk carrier ship are used to determine the unit energy cost. The results obtained from the analysis showed that the use of shoreside power has economic advantages. It is an important issue for shipowners and port authorities to reduce operating costs, fuel consumption and to decrease the environmental impacts of emissions.
Keywords: Ship; shoreside power; energy efficiency; energy cost; smart grid; RENEWABLE ENERGY; PORT; EFFICIENCY; EMISSIONS; IMPACT; PERSPECTIVES; TECHNOLOGIES; MANAGEMENT; REDUCTION; POLICIES; Transportation